Thin Films Photovoltaics - Zaidi, Beddiaf; Shekhar, Chander (IntechOpen, 2022)
Thin film photovoltaic-based solar modules produce power at a low cost per watt. They are ideal candidates for large-scale solar farms as well as building-integrated photovoltaic applications. They can generate consistent power, not only at elevated temperatures but also on cloudy, overcast days and at low sun angles.Thin film photovoltaics are second-generation solar cells produced by depositing one or more thin layers, or thin films, of photosensitive material on a suitable substrate such as glass, polymer, or metal. Thin film solar cells are based on various materials such as cadmium telluride (CdTe), copper indium gallium diselenide (CIGS), and amorphous thin film silicon (a-Si, TF-Si) are commercially used in several conventional and advanced technologies.